Energy Dissipation and Shear Rate with Geometry of Baffled Surface Aerator - Kumar, Bimlesh (Chemical Engineering Research Bulletin, 2010)
The geometric parameters of surface aeration systems govern the process phenomena. The dissipation rate of turbulent kinetic energy (ε) and shear rate (γ) are the key process parameters for mixing in surface aerators. Present work by doing numerical computation by visimix® analyzes the effect of geometric parameters (impeller diameter, cross-sectional area of the tank, liquid height, width of the baffle, rotor blade length and immersion height) on ε and γ. Analysis has been done by making the geometric parameters non-dimensionalized through rotor diameter. With an increase in liquid height and baffled width, there is an increase in the case of energy dissipation and shear rate values. In the case of tank area and blade length, it is vice versa. Energy dissipation and shear rate are not affected by the variation in immersion height of the impeller. Keywords: energy dissipation; mixing; shear rate; surface aerator DOI = 10.3329/cerb.v14i2.4910 Chemical Engineering Research Bulletin 14 (2010) 92-96